2008
DOI: 10.1016/j.bone.2008.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of extracellular matrix protein phosphorylation alters mineralization in differentiating chick limb-bud mesenchymal cell micromass cultures

Abstract: Protein phosphorylation and dephosphorylation are important regulators of cellular and extracellular events. The purpose of this study was to define how these events regulate cartilage matrix calcification in a cell culture system that mimics endochondral ossification. The presence of casein kinase II (CK2), an enzyme known to phosphorylate matrix proteins, was confirmed by immunohistochemistry. The importance of phosphoprotein phosphorylation and dephosphorylation was examined by comparing effects of inhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 63 publications
(144 reference statements)
3
28
0
Order By: Relevance
“…Therefore, the DPP phosphorylation pattern could be a code for the configurations of the peptides and hence their affinity for potential ligands. In previous studies, we showed the important role of phosphorylation in mineralized tissues and its role in the biomineralization process (17,18); this study showed the specific behavior of the DPP peptides when they are phosphorylated. The precise role of each of the peptide structures remains unclear.…”
Section: Discussionsupporting
confidence: 54%
“…Therefore, the DPP phosphorylation pattern could be a code for the configurations of the peptides and hence their affinity for potential ligands. In previous studies, we showed the important role of phosphorylation in mineralized tissues and its role in the biomineralization process (17,18); this study showed the specific behavior of the DPP peptides when they are phosphorylated. The precise role of each of the peptide structures remains unclear.…”
Section: Discussionsupporting
confidence: 54%
“…An indirect effect on the signal transduction pathways was ruled out, as IL-1-mediated MMP-1 expression was not hindered by dephosphorylation of intact cells. Reports show that ECM proteins (osteopontin, sialoprotein, dentin matrix protein-1, phosphophoryn) as well as many secretory proteins (casein, enkephalin precursor, progastrin, chromogranin) become phosphorylated during their movement through the secretory pathway (Boskey et al, 2008;Turner et al, 1993). In addition, the extracellular phosphorylation of the ectodomains of integral proteins is not unprecedented.…”
Section: Discussionmentioning
confidence: 99%
“…Levamisole reversibly but non-competitively inhibits ALP (39), and is a potent inhibitor of the calcification of osteoblasts (bone forming cells) (44,45) and VSMCs (19,46). The bisphosphonate etidronate, an inhibitor of hydroxyapatite formation, has also been reported to inhibit calcification of VSMcs and osteoblasts.…”
Section: Discussionmentioning
confidence: 99%